Saúde e doença na fisio-psicologia nietzschiana: o tipo Nietzsche contra o tipo Wagner - Bocalon, Estevão (2020)
The main subject of this research is the construction, on Nietzsche’s thought, of decadent type and the healthy type. The central problem consists in the possibility of overcoming the decadence throught the antagonism between the Wagner’s décadent type, built on The Wagner Case (1888), and the Nietzsche’s type in Ecce Homo (1888). This possibility implies another problem: how does the self-construction of a healthy type as expression of an affirmative state of forces, capable of overcoming the disease and achieving the great health occur? To investigate this question, we must understand the physio-psychology notion and aesthetics as applied physiology, important in Nietzsche’s research about Wagner’s artistic production. In this context, the German thinker develops his typology construction, because an artistic production is considered a symptom of a forces configuration, wich could be healthy or sick, décadent. Nietzsche sought to recognize the décadence signs also in himself, which implies the possibility, from Wagner’s decadent type, built in The Wagner Case, to glimpse the Nietzsche’s type in Ecce Homo, as a overrun of décadence. To understand the construction of this antagonistic type, if is a matter of choice or not, we should also approach the Nietzsche’s critic about the traditional notion of subject. It’s about whether there are some possible kind of intervention to create a healthy life-affirming forces configuration, It is intended, from that, point out that Ecce Homo isn’t an autobiographical work, but only written in this style: this book would have as its guiding thread the construction of an ideal Phylosopher model. A healthy type that was capable of became what it is. Thus, we investigate the possibility of Nietzsche’s type, in Ecce Homo, overrun the décadence expressed by his antipode: Wagner’s decadent type. The research of this theme is relevant, mostly for an enhanced understending of Nietzsche’s thinking and his reflections about the possibility of creating new cultures.